Implementasi Model Pembelajaran Group Investigation dalam Mata Pelajaran PAI Kelas X Multimedia di SMK YPT 2 Purbalingga - Fathurrohman Fathurrohman; Makhful Makhful (UM Purwokerto Press, 2023)
This article discusses Group investigation (GI) as a learning model with students studying in groups, study groups are formed based on the topics chosen by students. This approach requires more complex norms and structures than the more teacher-centered approach. In GI cooperative learning, students are divided into several groups with heterogeneous members of 2-6 students. The group chooses a topic to investigate and conducts an in-depth investigation of the chosen topic, then prepares and presents a report in front of the class. This study aims to determine of the implementation of the group investigation learning model and to find out the supporting and inhibiting factors in implementing the Group Investigation learning model in the class X PAI subject at SMK YPT 2 Purbalingga. This research uses qualitative research with descriptive methods. Data collection techniques using interview techniques, documentation, and observation. The data analysis technique uses data reduction, data presentation, and conclusion drawing. The results showed that the group investigation learning model in PAI subjects for class X Multimedia at SMK YPT 2 Purbalingga was that the teacher prepared the lesson plans and materials first. the teacher greets and attends to students after that a little adds material and gives direction to the students. Next, the teacher divides the class into several groups where each group is given different material for investigation, students search for material independently using books or the internet, each group represents 2 or 1 child to explain their learning outcomes and is responded to by other groups, the last one the teacher gives comments and conclusions. Supporting and inhibiting factors in implementing the group investigation learning model in PAI class X Multimedia subjects at SMK YPT 2 Purbalingga, namely the facilities and infrastructure for student learning are sufficient, while the inhibiting factor is that some students are not active in their groups.